Rethinking the Image of Women in Recent Nigerian Video-films: The Example of Chinwe Egwuagu’s Mr & Mrs - Edebor, Solomon (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
This paper attempts to interrogate the image of women presented to the Nigerian audience in recent Nigerian video-films against the backdrop of some earlier studies that affirm prejudiced and damaging portraitures of Nigerian women. Chinwe Egwuagu’s Mr & Mrs has been used as a representative sample of this new trend that projects women largely in positive light. The paper posits that there is, indeed, a need to further re-invent the image of women with a view to negotiating a better space for them, thereby ensuring gender balance. It, nevertheless, cautions against productions that will fall victims of negative, biased and/or inaccurate portrayals of the male gender, thus, rendering efforts of Nigerian video-filmmakers counter-productive.